Measuring Information Management at MCI Simulation: Instruments Evaluation and Comparison. Issue 1 (September 2020) - Perry, Omer; Jaffe, Eli; Bitan, Yuval
Introduction : Information management (also known as "communication" or "gathering and analyzing information") is one of the core tasks of MCI (Mass-Casualty Incident) commanders during the chaotic prehospital phase.1 To train EMS (emergency medical service) personnel on how to manage an MCI efficiently, simulation drills are conducted in which participant performance is evaluated. As such, varied instruments have been developed to measure information management quality during MCI simulations. Since every instrument could lead to different results, our goal at the current study was to evaluate what are the advantages of applying each one of the instruments. Methods : Three instruments were chosen for the current study: (1) The Self-Assessment Teamwork Tool for Students (SATTS), (2) a set of performance indicators aimed to be scored by an experienced observer, and (3) Dynamic Information Management Quantification Instrument (DIMQI) which allows quantifying information items. All instruments were applied to the same MCI simulation. Results and Conclusions : Applying each of the instruments yielded a different layer of information. Thus, researchers and instructors consider using all three instruments as they are complementary to each other.